Historical evolution and conceptual definition of differentiated instruction through scholarly lenses - Shareefa, Mariyam (Jurnal Pendidikan Bitara UPSI, 2025)
This study examines the concept of differentiated education through a systematic review of literature. A total of 66 pertinent studies were identified by using a multi-step process that involved keyword selection, database searches, and article screening. The historical development of differentiated instruction reveals its roots in the 18th century’s focus on individual needs and student-centered learning. However, a lack of consensus on a single definition exists, with scholars offering various conceptualizations that emphasize catering to student diversity and maximizing learning growth. This emphasizes the necessity of a precise and uniform definition to direct efficient application. The paper concludes by suggesting further research on how educators translate these definitions into classroom practices and the impact of different differentiation strategies on student learning outcomes.